2011
DOI: 10.1007/s10646-011-0661-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate of Pseudokirchneriella subcapitata exposed to herbicides found in surface waters in the Alqueva reservoir (Portugal): a bottom-up approach using binary mixtures

Abstract: Previous work showed the existence of ecotoxicity of water samples from the Alqueva reservoir due to the presence of the herbicides atrazine, simazine, terbuthylazine and metolachlor. In the present study we examine the effects of these herbicides singly and as binary mixtures on the growth rate of the microalgae Pseudokirchneriella subcapitata. Usually, the toxicity of mixtures is evaluated in relation to the reference models CA (concentration addiction) and IA (independent action). In this study CA model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The test species of green alga, Raphidocelis subcapitata, is considered a sensitive and environmentally relevant model. The results observed in the present study for the non-irradiated atrazine samples are comparable with the results of Van der Heever et al [24] who reported IC 50 359 mg/l, even though lower IC 50 values for the same species were reported by Weiner et al [25] and Pérez et al [26] (48.77 µg/l and 196 µg/l, resp.) Experiments with fish RTgill-W1 cells did not show any toxic effects in both non-irradiated and irradiated atrazine samples.…”
Section: Discussionsupporting
confidence: 91%
“…The test species of green alga, Raphidocelis subcapitata, is considered a sensitive and environmentally relevant model. The results observed in the present study for the non-irradiated atrazine samples are comparable with the results of Van der Heever et al [24] who reported IC 50 359 mg/l, even though lower IC 50 values for the same species were reported by Weiner et al [25] and Pérez et al [26] (48.77 µg/l and 196 µg/l, resp.) Experiments with fish RTgill-W1 cells did not show any toxic effects in both non-irradiated and irradiated atrazine samples.…”
Section: Discussionsupporting
confidence: 91%
“…The results observed in the study for the non-irradiated atrazine samples are comparable with the results of Van der Heever et al [53] who reported IC 50 385 μg/l, even though lower IC 50 values for the same species were reported by Weiner et al [54] and Pérez et al [55] (48.77 μg/l and 196 μg/l, resp. )…”
Section: Toxicity Tests For Triazine Herbicidessupporting
confidence: 90%
“…In the post-exposure period, five blanks with only algae and no daphnids were also prepared and maintained in the same conditions as the other beakers with daphnids, as previously describe for the exposure period. Feeding rates (cells/mL/ individual/hour) were determined in accordance with the method described by Allen et al (1995); algal concentration was measured using a colorimetric method at 440 nm for both exposure and post-exposure periods (Pérez et al, 2011). For triclosan tested concentrations were 100, 300, 500 and 700 mg/L and for carbendazim corresponded to 100, 165, 230, 295, 360 and 425 mg/L.…”
Section: Feeding Inhibition Test and Post-exposure Testsmentioning
confidence: 99%